Doxorubicin, vinblastine, dacarbazine and lenalidomide for older Hodgkin lymphoma patients: final results of a German Hodgkin Study Group (GHSG) phase‐I trial. (28th December 2018) - Böll, Boris; Plütschow, Annette; Bürkle, Carolin; Atta, Johannes; Pfreundschuh, Michael; Feuring‐Buske, Michaela; Vogelhuber, Martin; Sökler, Martin; Eichenauer, Dennis A.; Thielen, Indra; von Tresckow, Bastian; Fuchs, Michael; et al.
Summary: About 30% of all Hodgkin lymphoma (HL) patients are ≥60 years old. As lenalidomide has promising single agent activity in multiple relapsed HL, we replaced bleomycin in ABVD with lenalidomide in this phase‐I trial. Patients aged ≥60 years with early‐unfavourable‐ or advanced‐stage HL (Eastern Cooperative Oncology Group performance status ≤2, Cumulative Illness Rating Scale for Geriatrics score 0–7) received 4–8 cycles of AVD (doxorubicin, vinblastine, dacarbazine) and lenalidomide in escalation with overdose control. Dose‐limiting toxicities (DLTs) included thromboembolism ≥grade 2, severe haematological toxicity, neutropenic fever and prolonged therapy delay. Twenty‐five patients with a median age of 68 years were included, 68% had advanced‐stage HL. A pre‐defined stopping criterion for dose escalation after DLT evaluation of 20/24 patients suggested a recommended phase II dose (RPTD) of 20 mg. DLTs occurred in 10/24 evaluable patients, all treated with ≥20 mg, however, median relative dose intensity was 97% (interquartile range 49–104%). Grade 3 or higher toxicities occurred in all 22 patients at ≥20 mg lenalidomide but no treatment‐related deaths occurred. Overall response rate was 80% for all patients (20/25) and 86% (19/22) at ≥20 mg lenalidomide. Three‐year estimates for progression‐free survival and OS were 69·7% (95% CI: 50·3–89·1%) and 83·8% (95%‐CI: 69·3–98·4%), respectively. In conclusion, AVD with lenalidomide 20 mg is feasible and highly effective in older HL patients.